The influence of anti-COVID-19 measures on the incidence of hand-foot-mouth disease in Zhanggong district of Ganzhou city in China - Yixing Guo; Yuhan Zhu; Yihan Wang; Hui Yin; Laiye Han; Tian Zhong; Ying Xiao; Lawrence T. Lam; Xi Yu (Heliyon)
Objectives: In order to understand the efficacy of control measures and their impact on the prevention of Hand-foot-mouth disease, this study focuses on assessing the repercussions of the COVID-19 pandemic outbreak on the hand-foot-mouth disease prevalence. Methods: Descriptive epidemiological methods and an autoregressive integrated moving average model were employed to analyze the hand-foot-mouth disease incidence data in Zhanggong district of Ganzhou city in China from 2010 to 2019. Predictions for year 2020 and 2021 were extrapolated based on incidence series from 2010 to 2019. Subsequently, a comparative evaluation was undertaken between the predicted and actual values of the incidence of hand-foot-mouth disease during 2020 and 2021. Results: The annual average number of reported cases of hand-foot-mouth disease during the period from 2010 to 2021 was 2,027, and the annual incidence was 321.28 per 100,000 citizens in Zhanggong district of Ganzhou city. The autoregressive integrated moving average model (1, 1, 0) with smallest Bayesian information criteria value as 151.33 was chose for prediction. And the values of RMSE and MAPE were 775.54 and 32.7, respectively. The autoregressive integrated moving average model predicted 2640 cases above the observed count of 756 cases in 2020, and 463 cases above the observed count of 2140 cases in 2021. Conclusion: The disparity between the predicted values and the actual values for 2020 is larger than that for 2021. It is suggested that the COVID-19 prevention and control measures have a significant impact on reducing the incidence of hand-foot-mouth disease.